Green Composites Made of Bamboo Fabric and Poly (Lactic) Acid for Packaging Applications—A Review - M.R., Nurul Fazita; Krishnan, Jayaraman; Debes, Bhattacharyya; M.K., Mohamad Haafiz; Chaturbhuj K., Saurabh; M. Hazwan, Hussin; H.P.S, Abdul Khalil (MDPI, 2016)
Petroleum based thermoplastics are widely used in a range of applications, particularly in packaging. However, their usage has resulted in soaring pollutant emissions. Thus, researchers have been driven to seek environmentally friendly alternative packaging materials which are recyclable as well as biodegradable. Due to the excellent mechanical properties of natural fibres, they have been extensively used to reinforce biopolymers to produce biodegradable composites. A detailed understanding of the properties of such composite materials is vital for assessing their applicability to various products. The present review discusses several functional properties related to packaging applications in order to explore the potential of bamboo fibre fabric-poly (lactic) acid composites for packaging applications. Physical properties, heat deflection temperature, impact resistance, recyclability and biodegradability are important functional properties of packaging materials. In this review, we will also comprehensively discuss the chronological events and applications of natural fibre biopolymer composites.